2019
DOI: 10.1155/2019/5274598
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin and ABT-199 Coencapsulated Nanocarriers for Targeted Delivery and Synergistic Treatment against Hepatocellular Carcinoma

Abstract: For the patients with hepatocellular carcinoma (HCC), conventional chemotherapy is insufficient or has no benefit. Although combination chemotherapy has been proven as an efficient strategy to enhance anti-HCC efficacy, some barriers, such as low bioavailability and side effects, are limiting clinical development. In order to overcome disadvantages of combination chemotherapy in HCC, targeted nanoparticles (NPs) simultaneously loaded with doxorubicin (DOX) and ABT-199 in an optimal synergistic ratio were devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…This could be as a result of enhanced permeability and retention effect (EPR) of NPs in tumor tissue as well as short half-life of free drugs in biological systems. 41,42 On the other hand, using NPs for combination therapy could facilitate synergistic effects through the maintenance of the optimized loaded-drugs ratio and guarantee similar in vivo distribution of drugs. 6 In our previous study, 28 it was shown that the profile of GBA release from NPs was pH-dependent.…”
Section: Resultsmentioning
confidence: 99%
“…This could be as a result of enhanced permeability and retention effect (EPR) of NPs in tumor tissue as well as short half-life of free drugs in biological systems. 41,42 On the other hand, using NPs for combination therapy could facilitate synergistic effects through the maintenance of the optimized loaded-drugs ratio and guarantee similar in vivo distribution of drugs. 6 In our previous study, 28 it was shown that the profile of GBA release from NPs was pH-dependent.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison, active targeting can significantly improve the local drug concentration delivered through modifications of nanoparticles with affinity ligands to bind with receptors expressed on tumor cells. Studies have demonstrated target HCC therapies through different cell surface receptors (i.e., asialoglycoprotein receptor (ASGPR) [100], folate receptor [101], or CD44 [102]). Nevertheless, the majority of these receptors are common tumor biomarkers that are not HCC specific and cannot be used as predictive markers to monitor the therapeutic efficacy of nanomedicines.…”
Section: Therapeutic Challenges For Novel Technologies Targeting Oxidative Stress-dependent Pathways In Hccmentioning
confidence: 99%
“…In patients with advanced HCC however, doxorubicin administration failed to improve survival [5] . The combined effects of doxorubicin and sorafenib have been studied but favorable results were not obtained because of higher toxicity, mainly cardiotoxicity and neutropenia [102] .…”
Section: Doxorubicinmentioning
confidence: 99%